Incidence of Guillain–Barré syndrome in South Korea during the early COVID-19 pandemic - Choi, Sun Ah; Hwang, Junho; Lim, Byung Chan; Chae, Soo Ahn (Frontiers in Neurology, 2023)
Objectives: Guillain-Barré syndrome (GBS) is an immune-mediated polyradiculoneuropathy, often triggered by infection. We aimed to investigate how the incidence of GBS changed in the early stages of the coronavirus 2019 (COVID-19) pandemic, when nationwide infections declined due to non-pharmaceutical interventions. Methods: We conducted a nationwide population-based retrospective GBS cohort study using data from the Health Insurance Review and Assessment Service of Korea. New-onset GBS patients were defined as those who were first hospitalized with an International Classification of Disease, 10th Revision code for GBS (G61.0) as a primary diagnosis between January 1, 2016, and December 31, 2020. The incidence of GBS in the pre-pandemic years (2016-2019) was compared with that in the first pandemic year (2020). Nationwide epidemiological data for infections were collected from the national infectious disease surveillance system. A correlation analysis was performed to determine the incidence of GBS and nationwide trends of various infections. Results: Overall, 3,637 new-onset GBS cases were identified. The age-standardized incidence of GBS in the first pandemic year was 1.10 (95% confidence interval, 1.01-1.19) per 100,000 persons. Compared to the first pandemic year, the incidence of GBS during the pre-pandemic years (1.33-1.68/100,000 persons/year) was significantly higher with incidence rate ratios of 1.21-1.53 (P < 0.001). Nationwide cases of upper respiratory viral infections were significantly reduced in the first pandemic year, however, Campylobacter infections peaked in the summer of the pandemic. The nationwide epidemiology of parainfluenza virus, enterovirus, and Campylobacter infections correlated positively with GBS incidence. Conclusion: The overall GBS incidence decreased in the early stages of the COVID-19 pandemic, which can be attributed to the dramatic reduction in viral illnesses due to public measures.